2000
DOI: 10.1021/es0011212
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Ligands for the Ah Receptor and Sex Steroid Receptors in Hepatic Tissues of Fish Exposed to Bleached Kraft Mill Effluent

Abstract: Male white sucker (Catostomus commersoni) from a population exposed to effluent from a bleached kraft mill and from a reference site were held in effluent or clean water for 4 d. To investigate bioavailable bioactive compounds, hepatic tissues were extracted and fractionated according to octanol−water partition coefficient (K ow) using reverse phase HPLC. Fractions were tested in vitro for the presence of compounds functioning as ligands for (i) the aryl hydrocarbon receptor (AhR) using mixed function oxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 33 publications
5
53
0
1
Order By: Relevance
“…Thus, androstenedione is a good candidate for causing the observed masculinizations of mosquitofish; but the relative contribution of other steroid receptor ligands remains to be evaluated. Hewitt et al (37) showed that fish exposed to kraft pulp mill effluent accumulate androgen and estrogen receptor ligands in their livers. Taking the findings of induced male secondary sex characters into consideration, we have extensive evidence for the presence of masculinizing agents in pulp and paper mill effluents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, androstenedione is a good candidate for causing the observed masculinizations of mosquitofish; but the relative contribution of other steroid receptor ligands remains to be evaluated. Hewitt et al (37) showed that fish exposed to kraft pulp mill effluent accumulate androgen and estrogen receptor ligands in their livers. Taking the findings of induced male secondary sex characters into consideration, we have extensive evidence for the presence of masculinizing agents in pulp and paper mill effluents.…”
Section: Discussionmentioning
confidence: 99%
“…In a more restricted environment, such as in lakes or rivers, population effects are more likely to occur, whereas compensatory migration may be important on the coast over longer times. Several laboratories worldwide, including ours, are presently working on the identification of endocrine-disrupting substances in pulp and paper mill effluents (35)(36)(37)41,44). We hope the results from these studies will eventually enable an evaluation of possible technology adjustments in relation to the severity of the potential environmental consequences.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent improvement or recovery from 1994 is consistent with a significant reduction in dioxin concentrations in fish from the river since the conversion to ECF bleaching [22]. Dioxins have been shown to be associated with MFO induction in H4IIE cells incubated with extracts of livers of white sucker exposed to bleached kraft mill effluent [31]. Because data existed for only one year prior to conversion of the mills to ECF bleaching, however, it is not entirely certain that the responses seen in 1994 were the norm or that conditions had changed.…”
Section: Changes In Fish Responses Since Conversion To Ecfmentioning
confidence: 53%
“…About half of the sampled stations had relative concentrations of β-sitosterol in the sediments at or above the range that may affect reproductive parameters of fish (i.e., between 0.01 and 1.2 ppm β-sitosterol; MacLatchy & Van der Kraak, 1995;Mellanen et al, 1999;Tremblay & Van der Kraak, 1999;Hewitt et al, 2000). Some of these stations were associated with river mouths and pulp mill industries (B-6, P-7, A-1), but others were far from these influences (e.g., A-12; Fig.…”
Section: Sources Of Phytosterolsmentioning
confidence: 99%